Patient-reported health-related quality of life outcomes following mastectomy for breast cancer, with immediate, delayed or no breast reconstruction: Four-year follow-up from a prospective cohort study - Kathy Dempsey; Erin Mathieu; Meagan Brennan; Kylie Snook; Julia Hoffman; Ian Campbell; Jenni Scarlet; Heather Flay; April Wong; Frances Boyle; Madeleine King; Andrew Spillane (Breast, 2023)
Background: Breast reconstruction (BR) improves women's health-related quality of life (HRQOL) following mastectomy for breast cancer, yet factors contributing to improved HRQOL remain unclear. This study aimed to explore the overall impact of mastectomy with or without BR on participants' perceptions of HRQOL over time in a cohort of women with high-risk breast cancer; to examine differences in mean HRQOL scores between immediate BR, delayed BR and no BR groups; to assess the influence of patient characteristics potentially associated with HRQOL scores; and to determine the feasibility of long-term collection of patient-reported outcome measures in clinical settings. Methods: A prospective, longitudinal study of 100 women with high-risk breast cancer who underwent mastectomy with or without breast reconstruction and were likely to require post-mastectomy radiotherapy. Four validated patient-reported questionnaires, comprising 21 outcome measures relating to HRQOL, administered at baseline and up to 4 years post-mastectomy. Demographic, clinical and surgical data extracted from patient medical records. Results: Consistently significant declines in perceptions of future health and arm symptoms, consistently significant improvements in treatment side effects, breast symptoms and fatigue, as well as significant improvements, compared to baseline, in social functioning and financial difficulties at 48 months. No significant differences in mean HRQOL scores between women given a choice of reconstructive options. Conclusion: Similar trajectories of HRQOL scores were found in women with high-risk breast cancer who were offered a choice of BR. Informed choice may be an independent contributing factor in long-term maintenance of most HRQOL indicators at their pre-mastectomy levels.